The phenomenological body of liberature - Matuszyk, Łukasz (Hybris, 2016)
The paper poses the question about the corporeality of a liberary work. In the first part, the discussion is focused on the issue of a body, based on the phenomenological philosophy of Edmund Husserl and Maurice Merleau-Ponty. The second part presents the concept of liberature or, as it is often called, total literature. The last two sections are centred on the problem of the two types of a liberary “body,” as well as on the similarities between the phenomenological idea of the body and the corporeality of a liberary text.